2013
DOI: 10.1088/0953-2048/26/4/045012
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of the high strain tolerance of the critical current of DI-BSCCO tapes fabricated by means of the pretensioned lamination technique

Abstract: A remarkable improvement in the strain dependence of critical current and the mechanical properties of DI-BSCCO-Bi2223 tapes was achieved by means of the pretensioned lamination technique. In order to elucidate the origin of this high performance, the local strain exerted on BSCCO filaments was investigated by means of the synchrotron radiation technique. The relaxation strain A r was expressed by the sum of thermal strain and tensile strain in the fracture of BSCCO filaments. It was concluded that the central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 6 publications
5
18
0
Order By: Relevance
“…Our previous study revealed the pre-tension technique was also effective for improvement in the mechanical properties of Type HT-SS wires [9], [11]. Basically, the mechanical strengths of the laminated wires increased with higher pre-tension unless the filaments fracture.…”
Section: B Pre-tensionmentioning
confidence: 99%
“…Our previous study revealed the pre-tension technique was also effective for improvement in the mechanical properties of Type HT-SS wires [9], [11]. Basically, the mechanical strengths of the laminated wires increased with higher pre-tension unless the filaments fracture.…”
Section: B Pre-tensionmentioning
confidence: 99%
“…Moreover, to achieve the high current densities that are required to allow for sufficient margin for adding reinforcement to the mechanically relatively weak conductor, the reaction needs to take place at 25 to 100 bar in an oxygen-inert gas mixture [13, 26] (figure 1). There is presently discrepancy in the literature on whether densification of the Bi-2212 by overpressure reaction improves the allowable longitudinal strain limit beyond the 0.3 to 0.4% that is commonly observed in Ag/Ag-alloy matrix Bi-2212 and Bi-2223 wires and tapes [27, 28, 29, 30, 31, 32, 33, 34, 35]: Substrate-based experiments suggest no improvement and a 0.3% – 0.4% strain limit, whereas tensile tests suggest a 0.6% strain limit [36, 37, 38, 39]. That Bi-2212 is mechanically-weaker than both REBCO and high-strength Bi-2223 (below) is clear and there are recent attempts to diffusion-bond high-strength materials to aspected Bi-2212 wires to improve the allowable tensile stress from 120 to 150 MPa [39, 40] to more than 400 MPa [40].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Bi-2212, the brittle superconducting grains are embedded in a mechanically-weak Ag/Ag-alloy matrix. In Bi-2223, however, the mechanical properties are substantially improved [34, 35] (while retaining performance [45]) by soldering pre-tensioned stainless-steel (SS) or copper alloys (CA) onto the reacted tape. This lamination process was pioneered at American Superconductor Corporation [46, 47] and further optimized and commercialized by SEI.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows the tensile stress dependence of the critical current ratio Ic/Ic0. With a criterion of 95% [7,8], the tensile stresses δ95 for the original, 2-core, and 16-main-core samples were 750, 679, and 680 MPa, respectively. The latter is 91% of that for the original coated conductor, indicating that high tensile strength can be maintained after 15 iterations of the bending process for ESBS.…”
Section: B Critical Currents Of the Samplesmentioning
confidence: 99%